Surgical Outcome and Complication of Penile Fracture - Shaheer Ahmad Khan, Muhammad Shoaib Khan, Zeshan Ahmad, Iqbal Shahzad, Abdullah, Muhammad Mohsin Ayaz (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of current study is to determine the causes, symptoms of penile fracture and post-operative outcomes. Study Design: Prospective study Place and Duration: This study was conducted at multi centers at DHQ Teaching Hospital, KDA, Kohat and DHQ Hospital Batkhela during the period from February, 2022 to July, 2022. Methods: Total 30 patients had penile fracture were presented in this study. Included cases were aged between 20-50 years. After receiving informed written permission, detailed demographic information about the enrolled patients was compiled, including age, body mass index, place of residence, and marriage status. Causes and clinical features of fracture were assessed. Patients were underwent for surgery and success rate was observed. Post-treatment rate of complications among enrolled cases were also calculated. We used SPSS 22.0 version to analyze complete data Results: Included patients had mean age 35.7±12.32 years with mean BMI 24.7±4.31 kg/m2. Majority of the cases were married 26 (86.7%) and rest were unmarried 4 (13.3%). 12 (40%) patients had urban residency and majority were had rural 18 (60%). Most common cause of fracture was coital 20 (66.7%), followed by masturbation in 6 (20%) and 4 (13.3%) patients had manipulation during sleep. Deformity, swelling, detumescence and crackling sound was the most common symptoms. Right corpus was the most common tunical tear 24 (80%) and most common site was proximal 22 (73.3%). Success rate was found among 26 (86.7%) cases. Post-operatively complications were found among 5 (16.7%) cases in which plaques/ nodules, curvature, erectile dysfunction, pain and swelling were included. Conclusion: For the purposes of this study, we found the penis fracture to be a rather simple condition to diagnose. Cavernosography may be used to confirm a diagnosis if necessary. Penile fractures may be successfully treated with immediate primary surgical repair, resulting in normal erection without substantial sequelae. Short hospital stays and fast restoration of sexual function are common outcomes of this procedure. Keywords: Surgical Outcomes, Penile Fracture, Complications, Causes